Engineering Interventions in Sustainable Trickle Irrigation : Irrigation Requirements and Uniformity, Fertigation, and Crop Performance - Goyal, Megh R.; Aladakatti, Basamma K. (London : Taylor and Francis, 2017)
"Improving agricultural water use efficiency (WUE) is vitally important in many parts of the world due to the decreasing availability of water resources and the increasing competition for water between different users. Micro irrigation is an effective tool for conserving water resources. Studies have revealed a significant water savings, ranging from 40% to 70% under drip irrigation compared with surface irrigation. This new volume, Engineering Interventions in Sustainable Trickle Irrigation: Irrigation Requirements and Uniformity, Fertigation, and Crop Performance, presents valuable research that evaluates crop water and fertigation requirements, examines optimum irrigation and fertigation scheduling, and analyzes the performance of agricultural crops under micro irrigation. With an interdisciplinary perspective, this volume addresses the urgent need to explore and investigates the current shortcomings and challenges of water resources engineering, especially in micro irrigation engineering. The volume discusses crop water requirements, fertigation technology, and performance of agricultural crops under best management practices. The chapter authors present research studies on drip irrigated tomato, chilies, cucumber, eggplant, cabbage, garlic, sugarcane maize, cashew nut, sapota, banana, mango, and blueberries. Removing the research gap, this volume provides new information that will be valuable to those involved in micro irrigation engineering."--Provided by publisher.
part, 1 PART I: Crop Irrigation Requirements -- chapter 1 Water Requirements for Horticultural Crops under Micro Irrigation / Jayakumar Manickam Surendran Udayar Pillai Rajavel Manickam -- chapter 2 Water Requirement of Drip-Irrigated Tomato Inside a Shade Net House / Priyanka Sharma Mahesh Kothari Pradip Dalavi -- chapter 3 Optimized Irrigation Scheduling for Drip-Irrigated Tomato Using the Fao Aquacrop Model / Saranya Jeyalakshmi -- part, 2 PART II: Irrigation Application Uniformity -- chapter 4 Emitter Water Distribution Uniformity: Compensated Hydraulic Gradient / S. Vanitha S. Senthilvel -- chapter 5 Assessment of Coefficient of Uniformity And Distribution Uniformity of Mini Sprinklers / Amol B. Khomne R. C. Purohit P. K. Singh S. S. Burark -- chapter 6 Water Footprint in Drip- Irrigated Blueberries: Argentina / A. Pannunzio E. A. Holzapfel P. Texeira Soria F. Bologna -- part, 3 PART III: Fertigation Technology -- chapter 7 Efficient Nutrient Management Through Fertigation / Mahesh Rajendran Archana Irene -- chapter 8 Subsurface Drip Fertigation to Enhance Yield and Net Income of Sugarcane / Mahesh Rajendran Archana Irene -- chapter 9 Irrigation Scheduling Using Cropwat 8.0 and Level of Fertilizers for Maize Under Fully Automatic Drip Irrigation and Fertigation System / T. Arthi K. Nagarajan -- chapter 10 Cost Economics of Cucumbers Grown under a Shade Net House with Different Fertigation Levels / M. A. Patil S. B. Gadge Sunil D. Gorantiwar Arun D. Bhagat -- chapter 11 Fishpond Wastewater: The Potential Irrigation Source / Lala I. P. Ray B. C. Mal S. Moulick P. K. Panigrahi -- part, 4 PART IV: Performance of Agricultural Crops -- chapter 12 Performance of Tomato Under Best Management Practices / K. Nitha D. Tamilmani -- chapter 13 Performance of Drip-Irrigated Eggplant Under Best Management Practices / M. B. Vinuta S. V. Kottiswaran Basamma K. Aladakatti Truptimayee Suna -- chapter 14 Performance of Cabbage Under Best Management Practices / Vasantgouda Roti B. S. Polisgowdar P. S. Kashyap -- chapter 15 Performance of Chili (Capsicum Annuum L) Under Best Management Practices / A. Selvaperumal I. Muthuchamy -- chapter 16 Performance of Garlic Under Best Management Practices / Chandrika Patti Mallikajuna S. Ayyanagowdar Umapati satishkumar B. S. Polisgowdar Ashok Hugar -- chapter 17 Moisture Distribution Pattern Under Best Management Practices / Basamma K. Aladakatti K. Shanmugasundaram M. B. Vinuta Jagadeesha Mulagund -- chapter 18 Effects of different color Plastic mulches on growth and yield of banana / V. D. Paradkar N. N. Firake Sunil D. Gorantiwar -- chapter 19 Performance of Drip-Irrigated Mango, Sapota, and Cashew Nut / Ashok R. Mhaske.
Keywords: Crop Science; Water Engineering; TECHNOLOGY & ENGINEERING / Agriculture / General; TECHNOLOGY & ENGINEERING / Environmental / Water Supply